Growth of PdCoO2 by ozone-assisted molecular-beam epitaxy - Jiaxin Sun; Matthew R. Barone; Celesta S. Chang; Megan E. Holtz; Hanjong Paik; Jürgen Schubert; David A. Muller; Darrell G. Schlom (APL Materials, 2019)
We report the in situ, direct epitaxial synthesis of (0001)-oriented PdCoO2 thin films on c-plane sapphire using ozone-assisted molecular-beam epitaxy. The resulting films have smoothness, structural perfection, and electrical characteristics that rival the best in situ grown PdCoO2 thin films in the literature. Metallic conductivity is observed in PdCoO2 films as thin as ∼2.0 nm. The PdCoO2 films contain 180° in-plane rotation twins. Scanning transmission electron microscopy reveals that the growth of PdCoO2 on the (0001) surface of Al2O3 begins with the CoO2 layer.